Design of compact LC lowpass filters based on coaxial through-silicon vias array. (October 2021) - Yin, Xiangkun; Wang, Fengjuan; Pavlidis, Vasilis F.; Liu, Xiaoxian; Lu, Qijun; Zhang, Tao; Liu, Yang
Abstract: By utilizing coaxial through-silicon via (TSV) technology, compact L C low-pass filters (LPFs) are proposed. Firstly, several capacitors based on coaxial TSV are investigated, in detail, by means of analytic calculation, finite element method (FEM) simulation, and measurement. Secondly, a formula for the inductance of coaxial TSV-based spiral inductors is proposed and verified by FEM simulations and measurements. Finally, based on the investigation of TSV-based capacitors and inductors, an analytical model of the proposed L C LPFs based on 2 × 4, 2 × 5, 2 × 6, and 2 × 7 coaxial TSV arrays is proposed, and the equivalent circuit model and the finite element method (FEM) model are established in ADS and HFSS, respectively. The LPFs are fabricated and verified through measurements. In the proposed LPFs, coaxial TSVs are used as capacitors and inductors simultaneously, which leads to a more compact size. The parasitic capacitance of the inductors can, helpfully, induce a notch point for the proposed LPFs in stopband and improve the roll-off rate.